2014
DOI: 10.1016/j.jaci.2014.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Dedicator of cytokinesis 8–deficient patients have a breakdown in peripheral B-cell tolerance and defective regulatory T cells

Abstract: Background Dedicator of Cytokinesis 8 (DOCK8) deficiency is typified by recurrent infections, elevated serum IgE levels, eosinophilia, and a high incidence of allergic and autoimmune manifestations. Objective We sought to determine the role of DOCK8 in the establishment and maintenance of human B cell tolerance. Methods Autoantibodies were measured in the plasma of DOCK8 deficient patients. The antibody coding genes from new emigrant/transitional and mature naive B cells were cloned and assessed for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 47 publications
6
83
0
Order By: Relevance
“…We conclude that the restoration of WASp expression in HSCs of WAS patients after GT leads to the normalization of the central B cell tolerance checkpoint. who displayed decreased frequencies of Tregs, nonfunctional Tregs, or both (24,26,27,29). In agreement with these data, the defective peripheral B cell tolerance checkpoint in WAS patients was associated with Tregs displaying an abnormal phenotype and showing defect in homeostasis regulation and suppressive capacities.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We conclude that the restoration of WASp expression in HSCs of WAS patients after GT leads to the normalization of the central B cell tolerance checkpoint. who displayed decreased frequencies of Tregs, nonfunctional Tregs, or both (24,26,27,29). In agreement with these data, the defective peripheral B cell tolerance checkpoint in WAS patients was associated with Tregs displaying an abnormal phenotype and showing defect in homeostasis regulation and suppressive capacities.…”
Section: Discussionsupporting
confidence: 80%
“…A central B cell tolerance checkpoint, which depletes many polyreactive and antinuclear clones in the BM, appears to be mostly controlled by B cell intrinsic factors, since decreased BCR signaling and Toll-like receptor (TLR) 7 and 9 function lead to an impaired counterselection of autoreactive B cells (22)(23)(24)(25). On the other hand, peripheral B cell tolerance is mostly regulated by B cell extrinsic factors, such as regulatory T cells (Treg) (24,(26)(27)(28)(29). We thus investigated if the absence of WASp could affect central and peripheral B cell checkpoints, by evaluating the frequency of B cells expressing autoreactive antibodies at a single-cell level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the frequencies of antinuclear B cells were also elevated in AID-deficient patients (13.1% ± 5.4% in AID-deficient patients compared with 3.3% ± 2.2% in HDs, P < 0.001) ( Figure 1E). (2,18,20). In addition, both CD40L-and AID-deficient patients showed decreased peripheral blood Treg an incomplete correlation between serum BAFF concentration and B cell homeostatic expansion ( Figure 2C).…”
Section: Resultsmentioning
confidence: 97%
“…However, the impact of BAFF on the accumulation of autoreactive mature naive B cells remains unclear. While increased serum BAFF concentrations in CD40L-and AID-deficient patients as well as in CVID patients correlated with an altered peripheral B cell tolerance checkpoint, FOXP3-, SAP-, and DOCK8-deficient patients showed normal serum BAFF concentrations, despite increased frequencies of autoreactive mature naive B cells (2,7,8,15,16,18). We found that all CSR-D patients, who have no switched memory B cells, had a 2-fold increase in serum BAFF concentrations ( Figure 2B).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation